Role Ambiguity and Job Performance of Employees in the Service Sector SMEs in Malaysia (Malaysian Management Journal, 2011)
Small and medium size enterprises (SMEs) play a crucial role in the economic development of Malaysia, of which the majority are in the service sector. Employees of the service sector SMEs have often been associated with low level of job performance and past research has shown that there are many factors that can contribute to employee poor performance such as role ambiguity. Thus the aim of this study was to examine the relationship between role ambiguity and job performance of employees in the service sector SMEs in Malaysia. 1500 questionnaires were distributed and 300 were returned resulting in a 20% response rate. The result revealed that there was a significant relationship between role ambiguity and job performance of employees.